Innovative Approaches to SME Management: A Qualitative Review of Community Integration - Noch, Muhammad Yamin; Rumasukun, Mohammad Ridwan (Golden Ratio of Community Services and Dedication, 2023)
This study explores the role of community integration in Small and Medium Enterprises (SMEs) management, aiming to understand its impact on organizational resilience, innovation, and marketing effectiveness. Adopting a qualitative approach, the research employs semi-structured interviews and document analysis to gather data from diverse SMEs. Thematic analysis is utilized to identify patterns and themes in the data, facilitating the exploration of community integration dynamics and outcomes. The findings reveal that community integration enhances SMEs' access to resources, knowledge, and support systems, thereby contributing to their resilience and innovation capabilities. Moreover, active engagement with the local community positively influences SME marketing effectiveness and brand perception, fostering customer loyalty and market competitiveness. The study underscores the importance of strategic community engagement initiatives in creating shared value for both SMEs and their communities, emphasizing the need for tailored approaches that align with local contexts and stakeholder expectations. Overall, the research highlights the multifaceted nature of SME-community relationships and their implications for organizational strategy and societal impact.